An Independent Verification of Education Sector Data in Indonesia - Santoso, Javier Luque (World Bank, Washington, DC, 2021)
This document presents the first known systematic effort to assess the quality of the data gathered by MoEC and MoRA. To assess the accuracy of the data, unannounced visits were conducted to a representative sample of schools by a team of trained observers. These independent school observations were later compared with the official data records. This report compares collected data with the data in the respective ministry systems and identifies the shortcomings of current data management approaches in MoEC and MoRA, which might adversely affect data quality and subsequent decisions made using this information. This report was produced jointly by the World Bank, together with MoEC and MoRA. The World Bank received financial support from the Government of Australia’s Department of Foreign Affairs and Trade (DFAT) through the ‘Improving Dimensions of Teaching, Education Management and Learning Environment’ (ID-TEMAN) Trust Fund. This Trust Fund aims to support Indonesia to improve learning outcomes through better policy, operations, and implementation.